Soft power and foreign policy of the Russian Federation: some aspects of the present - Slavetsky В.Ю.; Mukhamadeyeva И.А.; Yelzhanova Е.Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The article is devoted to the analysis of the development and transformations of the Russian Federation foreign policy. Since the beginning of hostilities in Ukraine, the policy of Russia is undoubtedly one of the most researching areas in modern political science these days due to many practical aspects. It objectively dynamically develops and transforms in accordance with the promising new role of this state on the world stage. The purpose of the article is to determine the involvement of Soft power elements in their modernization and transformation in the further implementation of Russian foreign policy in the world space in the short and medium term. As a result, the article attempts to determine the main conceptual changes in Russian foreign policy and certain forecasts about the directions of possible upgrades and improvements in the translation and promotion of Soft power by the Russian side in the foreign policy space. In the course of the analysis, the authors came to the conclusion that the main participants in the political confrontation on the world stage in the near future will actively develop and improve the Soft power technology in their foreign policy. Objectively, they will also receive a new impetus to the development of methods and technologies for counteraction, strengthening their constant application in practice. Thus, the leading countries, including Russia, are drawn into a kind of "arms race" in the format of the unarmed advancement of their foreign policy interests.